2013
DOI: 10.1016/j.jval.2013.08.1371
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Psychiatric and Neurological Diseases in Patients with Workspace Mobbing Experience in Germany: A Retrospective Database Analysis

Abstract: Objectives: In recent years workplace mobbing attracts notice in public and science. Victims of workplace mobbing frequently suffer from depressions, somatic symptoms, may develop alcoholism or other substance abuse disorders and show increased risk of suicidal behavior. The aim of this study was to calculate the number of patients with a workspace mobbing documentation and their diagnosis profile in general practices in Germany between 2003 and 2012 based on the data from a large epidemiological database. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 0 publications
3
13
0
1
Order By: Relevance
“…Furthermore, severity of symptoms of depression (measured with BDI-II) and anxiety (measured with BAI), as well as pseudoneurology related complaints (measured with SHC), were also significantly higher compared to the other non-exposed patients and to the general Norwegian population (Statistics Norway, 2012;Indregard et al, 2013;Kjaergaard et al, 2014). Considering the detrimental effects caused by being exposed to bullying found in previous studies (e.g., Lahelma et al, 2012;Kostev et al, 2014;Lo Presti et al, 2019), the high levels of depressive and anxiety symptoms among these patients are not surprising. These findings are in accordance with previous research where exposure to workplace bullying have been associated with an increase in both depressive and anxiety symptoms (e.g., Verkuil et al, 2015;Lo Presti et al, 2019).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, severity of symptoms of depression (measured with BDI-II) and anxiety (measured with BAI), as well as pseudoneurology related complaints (measured with SHC), were also significantly higher compared to the other non-exposed patients and to the general Norwegian population (Statistics Norway, 2012;Indregard et al, 2013;Kjaergaard et al, 2014). Considering the detrimental effects caused by being exposed to bullying found in previous studies (e.g., Lahelma et al, 2012;Kostev et al, 2014;Lo Presti et al, 2019), the high levels of depressive and anxiety symptoms among these patients are not surprising. These findings are in accordance with previous research where exposure to workplace bullying have been associated with an increase in both depressive and anxiety symptoms (e.g., Verkuil et al, 2015;Lo Presti et al, 2019).…”
Section: Discussionmentioning
confidence: 79%
“…Exposure to workplace bullying has been established as a major source of distress and subsequently been identified as an important contributory factor to severe health problems in the working population (e.g., Kostev et al, 2014;Verkuil et al, 2015). A growing body of evidence has established that being exposed to such bullying tend to have a range of detrimental effects on victims, hence also being a major workrelated predictor of mental, psychosomatic and to some extent physical health problems (Vartia, 2001;Lever et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This was also demonstrated by Turner et al (2013) with regard to cyberbullying. With regard to coping behavior, compared to men, women seem to be more willing to (a) to report their mistreatment to authorities and friends and (b) seek help ( Unnever and Cornell, 2004 ; Kostev et al, 2013 ). Unnever and Cornell (2004) reported that girls found it easier to talk to their friends about victimization than to adults, who might rather be perceived as authorities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Einer europaweiten Erhebung zufolge hatten 4 % der abhängig beschäftigten Männer und 5 % der Frauen in den zwölf Monaten vor der Befragung Mobbing erlebt [13]. In einer deutschen, prospektiven Studie war der Gesundheitszustand von Mobbingopfern im Jahr vor Beginn des Mobbings schlechter als derjenige der Teilnehmer einer Vergleichsgruppe [14]. In einer norwegischen Studie waren psychische Probleme ein Risikofaktor, ein Opfer von Mobbing zu werden [15] [22].…”
Section: Mobbingunclassified